2017
DOI: 10.13083/reveng.v25i1.742
|View full text |Cite
|
Sign up to set email alerts
|

Equação De Hargreaves-Samani Calibrada Em Diferentes Bases Temporais Para Sete Lagoas, Mg

Abstract: Dados de evapotranspiração de referência (ETo) são requeridos em diversas análises relacionadas ao uso de recursos hídricos, como no manejo de irrigação, balanço hídrico de sequeiro, manejo de bacias hidrográficas, etc. O método FAO Penman-Monteith (FAO-PM) é considerado padrão para cálculo da ETo. Contudo, a aplicação deste método pode ser restringida pela falta de dados meteorológicos. Um dos métodos alternativos com menor requisição de dados é o Hargreaves-Samani (HS), o qual comumente necessita calibração … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The obtaining of improvements after the calibration of empirical methods was also reported by several authors, such as Patel et al (2015), Djaman et al (2016) andBorges Júnior et al (2017). Thus, calibration is an important tool to improve the performance of ET o estimation models, adapting them to local climatic conditions.…”
Section: Resultsmentioning
confidence: 59%
“…The obtaining of improvements after the calibration of empirical methods was also reported by several authors, such as Patel et al (2015), Djaman et al (2016) andBorges Júnior et al (2017). Thus, calibration is an important tool to improve the performance of ET o estimation models, adapting them to local climatic conditions.…”
Section: Resultsmentioning
confidence: 59%
“…From the evaluation of the performance index (PI) and Willmott's index of agreement (d) it was observed that all calibrations under study promoted an increasing of these indexes, with exception only for Paracatu with calibration A, where respectively values equal and less than those found for the not calibrated equation were obtained. It should be noted that, in most literature records, local calibration, performed in several ways, promotes better performances (Cobaner, 2011;Arraes et al, 2016;Borges Júnior et al, 2017 Table 5: Statistical indexes and classification for the Hargreaves-Samani equation not calibrated (HS) and calibrated by linear regression (Lin), adjustment of parameter "A" (A), adjustment of parameters "A" and "C" (AC), adjustment of parameters "A", "B" and "C" (ABC) and adjustment of parameters "A", "B" and "C" followed by calibration by linear regression (ABC+Lin).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to better estimate ET o , the local calibration is recommended (Borges Júnior et al, 2012;Feng et al, 2017). In Brazil, several authors calibrated HS equation for different locations (Arraes et al, 2016;Lima Junior et al, 2016;Borges Júnior et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This empirical method is notable for its wide use and is suggested by Allen et al (1998) and Pereira et al (2015) as an alternative to FAO-PM when only air temperature data are available. Due to the empirical nature of this method, there is a need for local calibration against the standard method with a view to gaining accuracy, even using machine learning techniques (Borges Júnior et al, 2017, Shiri et al, 2014, Shiri et al, 2015.…”
mentioning
confidence: 99%